2021
DOI: 10.1007/s10554-021-02316-x
|View full text |Cite
|
Sign up to set email alerts
|

Multi-modality assessment and role of left atrial function as an imaging biomarker in cardiovascular disease

Abstract: The left atrium (LA) plays a vital role in maintaining normal cardiac function. LA volume and function have been utilised as important imaging biomarkers, with their prognostic value demonstrated in multiple cardiac conditions. More recently, there has been a sharp increase in the number of publications utilising LA strain by echocardiography and cardiac magnetic resonance (CMR) imaging. However, little is known about its prognostic value or reproducibility as a technique. In this review, we aim to highlight t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 107 publications
1
9
0
Order By: Relevance
“…Spearman rank correlation coefficient showed that there is a relationship between LAVI and LVEF, that is consistent with the research data on the contribution of LA to LV function [33,34]. According to our study, only LAVI > 34 ml/m 2 is a risk factor for arrhythmia after TSA (Table 4).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Spearman rank correlation coefficient showed that there is a relationship between LAVI and LVEF, that is consistent with the research data on the contribution of LA to LV function [33,34]. According to our study, only LAVI > 34 ml/m 2 is a risk factor for arrhythmia after TSA (Table 4).…”
Section: Discussionsupporting
confidence: 91%
“…The findings confirm that LA remodeling and volume expansion reduces the effectiveness of TSA. It is possible that the presence of excess fibrous tissue (more than 20-30%) in the left and right atrium, as well as the presence of epicardial fat in the left atrium, affect the effectiveness of TSA [20,29,33,34]. We will present the results of research in this area in subsequent publications.…”
Section: Discussionmentioning
confidence: 99%
“…In CMR, the development of artificial intelligence techniques has reduced analysis time significantly, but this is not yet available for most atrial analysis techniques. Atrial strain, which is one of the most studied techniques in recent times and has also been included in imaging guidelines (86), is still limited due to measurement variability due to imaging modality, software, and operator factors (87).…”
Section: Discussionmentioning
confidence: 99%
“…The former can be calculated with 2D or 3D techniques from the atrial volumes in the different phases and the latter by speckle tracking or tissue Doppler imaging ( Figure 3 and Figure 4 ). The formulae for the calculation of the three atrial volumetric phases are included in Table 1 [ 23 , 24 , 25 , 26 , 28 ]. However, given the great variability of these parameters between individuals and pathologies, they are rarely used in clinical practice and are mainly applied in research studies [ 29 ].…”
Section: Multimodality Imaging Of the La Echocardiographymentioning
confidence: 99%